1995
DOI: 10.1159/000246553
|View full text |Cite
|
Sign up to set email alerts
|

Dermatomyositis with Follicular Hyperkeratosis

Abstract: We report 2 cases of dermatomyositis with follicular hyperkeratosis (FHK) in children. They occurred in a 10-year-old Vietnamese girl and a 9-year-old Caucasian boy. The girl’s FHK disappeared after 2 months of treatment. The boy presented, 15 months after the onset of his dermatomyositis, with a generalised FHK which lasted for 6 months. FHK can appear before, during or after dermatomyositis. It is more often generalised but can be localised. Erector pili myositis and ostial hyperkeratosis may be the explanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…However, Requena et al 5 described hyperkeratosis also involving the interfollicular epidermis. 7,8 Dupré et al 7 postulated that the hair follicle involvement with erector pili myositis might alter the hair cycle, result-ing in anomalies of the infundibular keratinization and subsequent follicular keratotic plugging. In rare instances, erector pili myositis has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Requena et al 5 described hyperkeratosis also involving the interfollicular epidermis. 7,8 Dupré et al 7 postulated that the hair follicle involvement with erector pili myositis might alter the hair cycle, result-ing in anomalies of the infundibular keratinization and subsequent follicular keratotic plugging. In rare instances, erector pili myositis has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Usually, these patients exhibit classical cutaneous lesions of dermatomyositis and stereotypical lesions of pityriasis rubra pilaris. [1][2][3][4][5][6][7][8][9][10][11][12] Usually, these patients exhibit classical cutaneous lesions of dermatomyositis and stereotypical lesions of pityriasis rubra pilaris.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperkeratotic skin eruptions are a rare manifestation of DM and only a few instances have been reported in the literature (12)(13)(14)(15)(16)(17)(18) (18). In Table 1, we summarize a literature review of patients with DM and cutaneous eruptions resembling PRP.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that Oriental patients are predisposed to such lesions. It is interesting that both of our patients and one described by de la Tribonniere et al (5) were Oriental.…”
Section: Discussionmentioning
confidence: 99%
“…These were biopsied in our second patient and the specimen showed a hyperkeratotic plugged follicle with a surrounding inflammatory cell infiltrate. De la Tribonniere et al (5) reported histologic changes suggesting arrector pili myositis. They suggested that this might be the mechanism by which follicular lesions arise in dermatomyositis.…”
Section: Discussionmentioning
confidence: 99%